2016
DOI: 10.4236/ajps.2016.77109
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Wood Density and Wood Fibre Characterization of Woody Species and Their Possible Utility in Northeastern Mexico

Abstract: Context: Preliminary screening has been undertaken by woody species of Tamaulipan thornscrub for wood density and its utilization northeastern Mexico for different purposes and to find possible relationship of density with wood fibre characteristics. This technique can be used in the selection of species with high wood density for possible utility. Aims: It is to determine the variability in wood density and in fiber cell morphology and its length and among wood species of the Tamaulipan thornscrub, northeaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
2
9
0
1
Order By: Relevance
“…But the opposite results were obtained from the study of Kojima et al (2009) in Gmelina arborea species. This shows the differences in the patterns of wood specific gravity that might occur among species as reported by Rodriguez et al (2016).…”
Section: Green Specific Gravitysupporting
confidence: 56%
“…But the opposite results were obtained from the study of Kojima et al (2009) in Gmelina arborea species. This shows the differences in the patterns of wood specific gravity that might occur among species as reported by Rodriguez et al (2016).…”
Section: Green Specific Gravitysupporting
confidence: 56%
“…The values of pellets density obtained in this work are similar to 1.12–1.3 g/cm 3 reported in The Pellets Handbook by Thek & Obernberger (2012) . Comparing wood density average, Rodriguez et al (2016) found that wood pellets density of A. wrightii , E. ebano and H. pallens increased 30%, 25% and 93%, respectively, which confirm that pelletization is a good process to increase the density even to denser species. The bulk density of the input material is an important factor in pelleting as the mills are fed by volume rather than weight ( Filbakk et al, 2011a ).…”
Section: Discussionmentioning
confidence: 62%
“…Besides that, the tearing strength and folding endurance of paper are indicated by the slenderness ratio [20]. Larger slenderness ratio results are better for paper making where it indicates a better formed and well-bonded paper [19,21]. Present results showed that the slenderness ratio of the four pioneer species is in the range of 36.4-50.2.…”
Section: Anatomical Propertiesmentioning
confidence: 88%